A PHILOSOPHICAL DESCRIPTION OF THE DYNAMICS OF THE CIVILIZATION MIGRATION OF POVERTY AND ITS SPECIFIC CHARACTERISTICS (Scientific journal of the Fergana State University, 2024)
The article examines the dynamics of civilizational migration of poverty, theoretical-methodological foundations, systematic-functional analysis, future tasks and directions of the poverty reduction strategy. Also, the dynamics of civilizational migration of poverty and its specific features are philosophically analyzed.